Perceptions on the Institutionalization of Public Participation in South Africa - Madue, Stephens (Mediterranean Journal of Social Sciences, 2012)
In democratic systems, public participation is understood to be complementary torepresentative democracy whereby regular parliamentary elections are held. The electedrepresentatives are expected to engage the public in decision-making processes to enhancetransparency and trust. Representative democracy additionally calls for the establishmentof public participation platforms for engaging the citizenry in all public affairs. Moreover,the rationale for public participation advocates for the public to actively participate in thedevelopment of plans at the formative stage, rather than after officials have committed toparticular choices. A self administered questionnaire survey was conducted to assess theperceptions of the Members of the Provincial Legislature, Parliamentary ConstituencyOfficers and administrative staff on how public participation has been institutionalized inthe Gauteng Provincial Legislature. The results of the survey show that the GautengProvincial Legislature is not adequately engaging its people in decision-making processesas per the constitutional mandate as provided for in the Constitution of the Republic ofSouth Africa, 1996. The research supports the notion that a direct democracy is not feasiblein modern nations, but it is important to have a model of democracy that will provide thebest possible degree of direct popular public participation.